New South American Lachesilla in the group forcepeta (Psocoptera: Lachesilidae) - García Aldrete, Alfonso Neri (Instituto de Ecología, A.C., 2000)
Fifteen species of South American Lachesilla in the group forcepeta are here described and illustrated. Two of them are endemic to Trinidad, nine occur in Brazil, with three endemics; two occur in Venezuela, with one endemic to that country, two occur in French Guiana, two occur in Ecuador, with one endemic to that country, one occurs in Bolivia and one is endemic to Colombia. Four species also occur outside of the South American subcontinent, in Costa Rica, Panamá, and México. The location of the types is given in each description.